Association between periodontitis and chronic kidney disease. Issue 1 (4th March 2022) - Parsegian, Karo; Randall, David; Curtis, Mike; Ioannidou, Effie
Abstract: Periodontitis and chronic kidney disease are chronic conditions with high community prevalence across the world. Patients with chronic kidney disease have been noted to have a high burden of periodontitis, and several shared risk factors have been associated with the prevalence and severity of both conditions. However, the precise relationship between the two conditions, and the extent to which each may contribute to the development of the other, remains a matter of debate. The goals of the present work were to: (a) provide the most current and relevant literature overview of the association between periodontitis and chronic kidney disease; (b) explore mechanisms underlying this association; and (c) determine if evidence exists for an independent association between these conditions. We also assessed whether improved oral hygiene and periodontal treatment could reduce the risk of developing chronic kidney disease and, if so, what protocols these strategies involve. Finally, we aimed to reveal gaps in our current knowledge to delineate the directions of future research. Although the exact relationship between these two conditions has not yet been defined, we highlight the importance of the interprofessional interaction between dental practitioners and the nephrology team and the importance of oral health assessment in the management of chronic kidney disease.